Optimization of Heat Transfer Performances Within Porous Solar Receivers—A Comprehensive Review - Guilong Dai; Yishuo Liu; Xue Chen; Tian Zhao (Energies)
The porous solar receiver (PSR) is a promising technology in advanced high-temperature applications. However, the non-uniform distribution of concentrated solar flux (CSF) and the dense pore structure lead to localized overheating and significant thermal losses for the PSR. This review focuses on the optimization strategies to enhance the thermal performance of the PSR, including porosity parameters, spectral selectivity, geometric configurations, and optical windows. Furthermore, mitigation strategies for addressing localized high temperatures in the PSR were thoroughly discussed, including methods for homogenizing CSF and improving the velocity of heat transfer fluid (HTF). Additionally, a numerical simulation and experimental measurements were introduced and evaluated. Additionally, the paper emphasizes the need to optimize the macroscopic geometry of OPSRs to improve their flow and heat transfer performance, thereby enhancing their practical value. It also suggests designing PPSRs that integrate adjustments for HTF mass velocity, CSF, optical window load, and reflection losses. Consequently, future studies should focus on developing efficient simulation and validation methods to advance the practical application of PSRs.